HAV Matrix: Employee Development in PT. X based on Potential Review Assessment - Nadia Shafira Putri; Endah Mastuti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The individual assessment potential review was conducted as part of talent management activities to obtain a comprehensive understanding of the individual’s potential and to identify competencies that require improvement. In addition to providing psychological measures to map employee profiles, the organization also considered performance evaluation results. The tool used in this assessment was the HAV Matrix. The subject of this study was an employee of PT. X. This research employed two data collection methods: psychological testing tools and interviews. At the end of the process, counseling sessions were conducted to provide developmental suggestions tailored to the individual’s needs through counseling programs, aiming to enable the individual to perform optimally. The research findings indicated that the subject falls into the